WORKSHOP PENINGKATAN JIWA WIRAUSAHA GUNA MENAMBAH NILAI EKONOMI KELUARGA MELALUI PEMANFAATAN POTENSI DAERAH - Dwi Yanuarindah Putri; Fidyah Jayatri; Triwilujeng Ayuningtyas; Roni Wiranata (JPM PAMBUDI, 2020)
The purpose of this PKM activity is a workforce that has not worked in Bedayu village, Senduro sub-district, Lumajang Regency. So far, entrepreneurship has been conveyed only through socialization to increase public awareness about the importance of entrepreneurship as a way to reduce high unemployment. But in reality socialization alone is not enough to make people motivated and interested in entrepreneurship. The method of implementing the PKM Economic Education Study Program embodies the entrepreneurship workshop program in a combination of hard skills and soft skills in the form of a combination of educational socialization about entrepreneurship and training to manage the potential of the Bedayu village area to improve the economic status of the community. The human resource competency program (hardskill) is related to how to cultivate the potential of the Bedayu community. While soft skills are related to the development of simple entrepreneurship that can be done in the easiest way accompanied by how to package and calculate the profits to be gained. The result of community service activities is the achievement of soft beds from the Bedayu village community for their interest in carrying out home-based entrepreneurial activities by creating business opportunities in the form of coffee products and marketing outside the Bedayu region